Health professional student’s volunteering activities during the COVID-19 pandemic: A systematic literature review - Umar, Tungki Pratama; Samudra, Muhammad Galang; Nashor, Kemas Muhammad Naufal; Agustini, Dessy; Syakurah, Rizma Adlia (Frontiers in Medicine, 2022)
Background The Coronavirus Disease 2019 (COVID-19) crisis has forced health and education services to use additional human resources, such as health professional students. Students in the health professions, particularly those in the medical field, can participate in a variety of voluntary activities, both directly and indirectly in health services. The aim of this review was to determine the affecting factors, types of activity, and benefits of undertaking a volunteering role by the health professional student. Methods A systematic review of health professional student volunteering during the COVID-19 pandemic was conducted using seven databases: Epistemonikos, ProQuest, Scopus, EBSCOhost, JSTOR, Cochrane Library, and PubMed. This literature search included published articles from March 2020 through to December 2021 using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines. Result We included 41 studies that met the selection criteria that assessed the factors and specific programs related to health profession students’ volunteering involvement during the COVID-19 pandemic era. The most frequently observed supporting factor of the eagerness to be a volunteer was the feeling of moral responsibility (such as social dedication, sense of duty, and care), potential learning opportunities, personal interest, and financial compensation. Factors that contributed to a person’s refusal to participate in a volunteer position were the fear of COVID-19 itself (such as transmission, risk of being infected, and personal identification as a risk group). Conclusion The review of available literature has shown that understanding the motivation and barriers to the willingness of health professional students to volunteer and the impact of volunteering activities on their future lives is a key for supporting them.